A Simulation of fish transport under optimal halth conditions - ا.م.د. عبد الامير رحيم جاسم / ا.م.د. عامر عبدالله جابر / ا.د. سالم عبد مطلك الدراجي / عباس خلف علي / خالد حمد حسوني / صابر حسين صبر ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2019)
The study was conducted at the fish farming station of marine science center University of Basrah, Iraq. 1 ton of viberklass tanks with special specification were used for fish transport of Common carp fish (Cyprenus carpio ). One experience tank (control tank) with natural ventilation (oxygen by pump) and without any additions are prepare, While other tanks supplied (experience tanks) with pure oxygen and salt as additions experience, special bottles oxygen used that is dissolved in water by stones ventilation and added different Anesthetic of QUINADIN2-Mathylauinoline dope µl 2/liter water after mixing with ethanol by 2 part of the substance to 1 part of alcohol methanol with salt 250 g/100 as added. 6 different concentrations are attended the laboratory experience (125 maikroltr/l-3 maikroltr/l), equal numbers of fish are put in each concentration, the behavioral situation of the fish was a note pinned to each concentration during different periods in terms of responding to the catalyst and swim fins movement and stagnation on the bottom and rates Breathing and the number of deaths and recover in order to get the best concentration can be used to fish without having any physiological case abnormality on fish and its mortality . The rates of fish lengths and weights are equal to 7.6 cm and 6.37 mg. 2000 fish from common carps C. carpio are usesd in the experience tank and the same number of fish in the control tank where the volume of water in each tank are 100 litres. The first tank are prepare with electrically operated air pump and close the tub tightly relative, either the other tank is powered by oxygen bottles of pure oxygen under pressure of 2 bar and an average temperature of 32 m. Fish behavior was noticed and the mortality cases in both tanks . The experiment lasted for three hours. Returned the first experience of control and experience tanks but 100% increase in the density of fish pond where she was placed in ordinary carp fish 4000 for three hours under the same conditions used in the first experiment. The results of the first experiment when using 2000 fish/100 l in 32 degrees Celsius after hours to fish swim naturally within the water column and there is no sign of stress. Not show mortality, where fish swim very naturally and do not suffer from any problem and was 100% survival rate after three hours of experience in control and experience. Salinity and acidity were within levels that began. The second experience at double density fish, different results especially in the control of where the fish were exhausted after only an hour of trial and the fish were swimming near the surface and irregularly then became more stressful with time, fish and swim in lopsided 40% survival rate after the end of the experiment. Either fish in experiment study it was swimming around a quiet and regular and showed no sign of stress was 100 percent survival rate after the end of the experiment.